CHARACTERISTICS AND PRINCIPLES OF THE DEVELOPMENT OF FINANCIAL SERVICES IN THE REGION (Marketing Journal, 2025)
This article examines the peculiarities and principles of financial services development in the region, presenting a classification of organizational principles (transparency, convenience, security through data protection, client -orientation, legality) and economic principles (reliability, fairness, financial literacy, economic efficiency, risk regulation) of financial services provision.
Keywords: Financial service; financial market; organizational -economic; banking; insurance; monetary policy; fiscal policy; foreign trade policy